The Role of Entrepreneurial Attitude as a Moderating Variable in the Influence of Government Support on Business Success in Surabaya - Mirza Esvanti; Sudarmiatin Sudarmiatin; Ludi Wishnu Wardana (Green Inflation: International Journal of Management and Strategic Business Leadership, 2024)
Business success is often influenced by various external and internal factors, including Government Support and Entrepreneurial Attitude from business actors. This study aims to analyze the influence of Government Support on Business Success on business actors in Surabaya, focusing on Entrepreneurial Attitude as a moderation variable. A quantitative approach was used in this study, involving a survey of 250 MSMEs in Surabaya as a research sample. Data was collected through questionnaires and analyzed using the SEM model with the Smart PLS data processing tool to determine the extent to which Entrepreneurial Attitude mediates the relationship between Government Support and Business Success. The results of the study show that Government Support has a significant positive influence on Business Success. In addition, Entrepreneurial Attitude strengthens this positive influence, where business actors with a high Entrepreneurial Attitude tend to be more able to take advantage of Government Support to achieve business success. These findings emphasize the importance of developing an Entrepreneurial Attitude in strengthening the effectiveness of Government Support for business actors. The practical implications of this study indicate that government policies should consider aspects of developing Entrepreneurial Attitude to encourage sustainable Business Success.